2011
DOI: 10.1371/journal.pone.0027867
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine Exposure by Toxoplasma gondii Is Fundamental to Balance the Immune Response Granting Survival of the Parasite and of the Host

Abstract: Phosphatidylserine (PS) exposure on the cell surface indicates apoptosis, but has also been related to evasion mechanisms of parasites, a concept known as apoptotic mimicry. Toxoplasma gondii mimics apoptotic cells by exposing PS, inducing secretion of TGF-beta1 by infected activated macrophages leading to degradation of inducible nitric oxide (NO) synthase, NO production inhibition and consequently persisting in these cells. Here PS+ and PS− subpopulation of tachyzoites were separated and the entrance mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 31 publications
(52 reference statements)
0
38
1
1
Order By: Relevance
“…Santos et al already showed that phosphatidylserine exposure by Toxoplasma gondii is fundamental for granting survival of the parasite in murine macrophages. 7 In concordance, phagocytosis of apoptotic cells by macrophages plays a role in Trypanosoma cruzi persistence. 6 Indeed, we have also found that during Leishmania infection, disease development relies on the presence of apoptotic-like promastigotes as infection of mice with only viable Leishmania promastigotes does not result in disease development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Santos et al already showed that phosphatidylserine exposure by Toxoplasma gondii is fundamental for granting survival of the parasite in murine macrophages. 7 In concordance, phagocytosis of apoptotic cells by macrophages plays a role in Trypanosoma cruzi persistence. 6 Indeed, we have also found that during Leishmania infection, disease development relies on the presence of apoptotic-like promastigotes as infection of mice with only viable Leishmania promastigotes does not result in disease development.…”
Section: Discussionmentioning
confidence: 99%
“…5 In agreement, apoptotic cells exacerbate parasite growth in Trypanosoma cruzi infection and phosphatidylserine exposure by Toxoplasma gondii is fundamental for granting intracellular survival, in macrophages. 6,7 Macrophages also serve as host cell for Leishmania parasites and act as antigenpresenting cells, in which phagosomal and autophagosomal maturation are involved in major histocompatibility complex (MHC) loading. In addition to the well-known endogenous MHC loading pathway, recent efforts have shed light on the involvement of autophagy-related proteins in antigen presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Once within the PV, T. gondii continues its stealth-like state by inducing the production of the antiinflammatory cytokines interleukin 10 (IL-10) and transforming growth factor beta (TGF-␤), inhibiting the production of the proinflammatory cytokines interleukin 12 (IL-12) and tumor necro- sis factor alpha (TNF-␣), and slowing its recognition by blocking major histocompatibility complex class II (MHC-II) expression (24)(25)(26)(27)(28). Apoptotic body mimicry through the parasite surface expression of phosphatidylserine may facilitate the production of TGF-␤ and the degradation of induced nitric oxide synthase (iNOS) (29). Additionally, T. gondii maintains a favorable host cell state by inhibiting the programmed cell death of infected cells and inducing leukocyte apoptosis (30)(31)(32).…”
Section: Toxoplasmosis Life Cycle and Mechanisms Of Virulencementioning
confidence: 99%
“…Primary peritoneal macrophages were isolated from CD11b knockout (CD11b 2/2 ) and wild-type (CD11b +/+ ) mice using the method modified from a previous report. 41 Briefly, mouse peritoneal macrophages were isolated by peritoneal lavage and purified by removing nonadherent cells after 1 hour of culture in complete medium with 10% fetal bovine serum. Macrophages were maintained in Dulbecco's modified Eagle's medium containing 4 mM L-glutamine, 4500 mg/L glucose, 1 mM sodium pyruvate, 1500 mg/L sodium bicarbonate, and 10% fetal bovine serum.…”
Section: Cell Culturementioning
confidence: 99%